2004
DOI: 10.1300/j156v05n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Competitive Advantage in a Deepening Crisis

Abstract: This paper examines how Export Processing Zone firms in Zimbabwe have responded to the economic crisis in Zimbabwe. The study investigated how exporters are responding to dissipating competitive advantages. Data was collected from a sample of 30 firms. It was analysed through factor analysis to extract constructs considered competitive advantages or disadvantages. Results show competitive advantages pursued are centred on three key factors, i.e., production, pricing, and product. Competitive disadvantages are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In the worst case, temporarily terminating agency business and changing to do other businesses are seriously considered. In conclusion, it showed that the agencies adopt all kinds of strategies for their survival, especially immediate strategies while, long-term strategies such as cost restructuring, mergers, and acquisitions, portfolio diversification, or product quality are neglected in this stage, which conforms to the findings of Muranda, 2004 andSchuh, 2012. It is interesting that during the ongoing-crisis of the COVID-19 pandemic, an unethical strategy like encouraging tenants to move to new places is pursued as similar to the study of Kabonga (2020) In the post-crisis stage, whose end we are still unsure of, it is predicted that many agencies will have learned their lessons about managing uncertainty and risks during a business crisis. To allocate the business risk, the agencies are more predisposed towards offensive and internal process change strategies such as acquiring new customers and products, carrying out more marketing activities, cash reservation, and productivity management in aim to deal with the next crisis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the worst case, temporarily terminating agency business and changing to do other businesses are seriously considered. In conclusion, it showed that the agencies adopt all kinds of strategies for their survival, especially immediate strategies while, long-term strategies such as cost restructuring, mergers, and acquisitions, portfolio diversification, or product quality are neglected in this stage, which conforms to the findings of Muranda, 2004 andSchuh, 2012. It is interesting that during the ongoing-crisis of the COVID-19 pandemic, an unethical strategy like encouraging tenants to move to new places is pursued as similar to the study of Kabonga (2020) In the post-crisis stage, whose end we are still unsure of, it is predicted that many agencies will have learned their lessons about managing uncertainty and risks during a business crisis. To allocate the business risk, the agencies are more predisposed towards offensive and internal process change strategies such as acquiring new customers and products, carrying out more marketing activities, cash reservation, and productivity management in aim to deal with the next crisis.…”
Section: Discussionsupporting
confidence: 76%
“…It is about changing an individual or an organization's existing functions to survive (Blackman & Ritchie, 2008;Mikusova & Horvathova, 2018;Schuh, 2012;Vargo & Seville, 2011). As an economic crisis sweeps the nation, the existing strategies such as product quality and product pricing are immediately jeopardized due to cost concerns, and the management must find alternative ways to instantly create strategic plans (Muranda, 2004;Schuh, 2012). Subsystems of preparation for a crisis are composed of the four approaches as passive, defense, challenge, and termination of the business with the two expected results of survival and maintaining the business's existence (Mikusova & Horvathova, 2018).…”
Section: Crisis Management Strategiesmentioning
confidence: 99%